2009
DOI: 10.1007/s11248-009-9275-y
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic zebrafish line with over-expression of Hedgehog on the skin: a useful tool to screen Hedgehog-inhibiting compounds

Abstract: We generated a transgenic line Tg(k18:shh:RFP) with overexpression of Sonic hedgehog in the skin epidermis. By 5 day-post-fertilization (dpf), many epidermal lesions were clearly observed, including a swollen yolk sac, epidermis growth malformation around the eyes and at the basement of the pectoral fins. Skin histology revealed embryos derived from Tg(k18:shh:RFP) displayed an elevated Nuclear/Cytoplasmic ratio and pleomorphic nuclei compared to their wild type littermates, suggesting the abnormal growth patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Founder fishes (F0) were either crossed with WT or crossed with each other to produce F1 embryos. Of and 4.9% (6 positive of 121) of embryos expressed RFP at 2 dpf, suggesting that the transgenic founder is a germ-line mosaic, which is a common finding in transgenic fish in the founder generation (Wang et al 2006c;Chen et al 2009a). The F2 segregation frequencies for these transgenic lines ranged from 48.6 to 53.2%, indicating a single insertion site of transgene for each line.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Founder fishes (F0) were either crossed with WT or crossed with each other to produce F1 embryos. Of and 4.9% (6 positive of 121) of embryos expressed RFP at 2 dpf, suggesting that the transgenic founder is a germ-line mosaic, which is a common finding in transgenic fish in the founder generation (Wang et al 2006c;Chen et al 2009a). The F2 segregation frequencies for these transgenic lines ranged from 48.6 to 53.2%, indicating a single insertion site of transgene for each line.…”
Section: Resultsmentioning
confidence: 97%
“…Our previous study showed that up-regulation of ptmaa is a consequence of hedgehog (Hh)-induced disorganized basaloid growths in the skin (Chen et al 2009a). To generate stable transgenic lines for further study of the physiological roles of ptmaa in skin development and skin carcinogenesis, embryos were injected with pZK18-Ptmaa-RFP and those with RFP expression were collected and raised to adulthood.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the transgenic zebrafish line Tg(k18:shh:RFP), Chen et al (2009) also demonstrated that the treatment using cyclopamine, a chemical, that is, known to suppress the hedgehog gene, is able to enhance and prolong the survival rates and survival durations of the transgenic embryos. In our laboratory, a preliminary experiment was conducted by treating the mifepristone-induced kras v12 transgenic fry with PD98059, an inhibitor of the kras downstream kinase MEK1.…”
Section: Transgenic Zebrafish Tumor Models: Bringing New Light To Drumentioning
confidence: 98%
“…Similar to the findings of , the rate of apoptosis in the thymus was reduced and the incidence of leukemia was dramatically increased when bcl-2 was also expressed. In 2009, another group generated a transgenic zebrafish line Tg(k18:shh:RFP) with over-expression of Sonic hedgehog in the skin epidermis and observed abnormal epidermal growth by 5 day post fertilization (Chen et al, 2009). With the availability of different transgenic lines, it is therefore possible to study how individual pathway crosstalk leads to tumorigenesis in vivo.…”
Section: Narrowing Down the Targets: Signaling Pathwaysmentioning
confidence: 99%